Contraceptive Methods Selection in Women of Childbearing Age (WUS) in South Sulawesi Province - Ningsih, Nining Ade; Latu, Saparuddin; Herawati, Dewi Marhaeni Diah; Syahruddin, Akmal Novrian (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The primary challenge in the population domain is the presence of a large population with a relatively high growth rate. This study aims to ascertain the distribution of modern contraceptives and identify the variables influencing the selection of contraceptive methods among women of childbearing age. The research employed an analytical cross-sectional study design, utilizing bivariate analysis (chi-square test) and multivariate analysis (logistic regression test) for data analysis. The study used secondary data from the 2019 SKAP. The population and research sample were taken based on the cluster approach as an enumeration area. This study takes all women of childbearing age (15-49 years) based on selected clusters in South Sulawesi Province. Among the participants, 205 (25.6%) chose Long-Term Contraceptive Methods (MKJP), while 599 (74.4%) opted for Non-Long-Term Contraceptive Methods (Non-MKJP). Bivariate analysis revealed three variables significantly associated with the choice of contraceptive method: education level, parity, and husband's support (p-value < 0.05). In the logistic regression test utilizing the backward method, the Odds Ratio (OR) values were obtained: for parity (OR = 1.683), signifying that women with child parity >2 were 1.683 times more likely to use MKJP compared to those with parity 2; for husband's support (OR = 1.733), indicating that women receiving husband's support had 1.733 times the likelihood of using MKJP compared to those without husband's support; and for education level (OR = 2.008), suggesting that those with a higher education level were 2.008 times more likely to use MKJP compared to those with lower education. The sequence of related variables influencing contraceptive choice was education level, followed by husband's support, and then parity percentage.